2015
DOI: 10.1007/s00415-015-7827-z
|View full text |Cite
|
Sign up to set email alerts
|

Regional covariance of muscarinic acetylcholine receptors in Alzheimer’s disease using (R, R) [123I]-QNB SPECT

Abstract: Alzheimer's disease (AD) is characterised by deficits in cholinergic neurotransmission and subsequent receptor changes. We investigated (123)I-iodo-quinuclidinyl-benzilate (QNB) SPECT images using spatial covariance analysis (SCA), to detect an M1/M4 receptor spatial covariance pattern (SCP) that distinguished AD from controls. Furthermore, a corresponding regional cerebral blood flow (rCBF) SCP was also derived. Thirty-nine subjects (15 AD and 24 healthy elderly controls) underwent (123)I-QNB and (99m)Tc-exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 61 publications
3
10
0
1
Order By: Relevance
“…This was characterized by reduced cholinergic activity. The reduced DMN activity of nAChRs is consistent with the previously reported findings of reduced M1/M4 mAChR expressions within similar regions [46]. These observations highlight the potential role of both types of receptors in AD and the potentially more fundamental role of the cholinergic system in normal functioning of the DMN network.…”
Section: Cholinergic Receptor Imaging: Exploring Brain Networksupporting
confidence: 91%
See 1 more Smart Citation
“…This was characterized by reduced cholinergic activity. The reduced DMN activity of nAChRs is consistent with the previously reported findings of reduced M1/M4 mAChR expressions within similar regions [46]. These observations highlight the potential role of both types of receptors in AD and the potentially more fundamental role of the cholinergic system in normal functioning of the DMN network.…”
Section: Cholinergic Receptor Imaging: Exploring Brain Networksupporting
confidence: 91%
“…A spatial covariance study of M1/M4 mAChRs in AD using [ 123 I]QNB SPECT showed concurrent decreased binding in medial temporal, basal forebrain, inferior frontal, and cingulate relative to simultaneously increased binding in the frontal poles, occipital, pre-post central, precuneus and superior parietal areas [46]. This pattern may suggest a loss of M1/M4 mAChR in the medial temporal and cholinergic rich basal forebrain, accompanied by either preservation or an increase in cortical M1/M4 mAChR binding.…”
Section: Cholinergic Receptor Imaging: Exploring Brain Networkmentioning
confidence: 99%
“…One study reported convergences of amyloid deposition, metabolic disruption, and atrophy of the DMN in AD (Buckner et al., 2005), suggesting that the relative decreased pattern within this network could be in fact characterizing these pathological and/or functional deficits, although an element of concomitant DMN cholinergic dysfunction cannot be excluded. Reduced DMN activity of nAChRs was consistent with our previous findings of reduced M1/M4 mAChR expressions within similar regions (Colloby et al., 2015), highlighting the potential role of both types of receptors in AD and that the cholinergic system may have a more fundamental role in the normal functioning of the DMN. Other mappings onto established resting-state networks, included the anterior insula and anterior cingulate, which are key nodes of the “salience network,” for initiation of cognitive control and switching networks to aid access to working memory and attention resources (Menon and Uddin, 2010, Seeley et al., 2009).…”
Section: Discussionsupporting
confidence: 93%
“…We derived disease-related α4β2 nAChR and rCBF patterns of spatial covariance, which implies the presence of several dysfunctional cholinergic and perfusion networks in AD. These findings represent the first attempt to differentiate AD from controls through spatial covariance analysis of cholinergic nicotinic receptor activity and/or availability, and follow our multivariate assessment of M1/M4 mAChR binding in AD (Colloby et al., 2015). …”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation